STRUKTUR KOMUNITAS DAN KELIMPAHAN MIKROALGA SEBAGAI BIOINDIKATOR KUALITAS PERAIRAN DI PELABUHAN SUNGAI DUKU PEKANBARU - Arliana, Fizza (FKIP Universitas Tanjungpura, 2025)
Port waters often face ecological pressures from shipping, industry, and settlements that can affect environmental quality. This study aims to analyze the community structure, abundance, and role of microalgae as bioindicators of water quality in the Duku River Port, Pekanbaru. This location was chosen because of its potential for quality decline due to anthropogenic activities. Sampling was conducted at three stations using survey methods and purposive sampling techniques. The results showed that microalgae abundance ranged from 1,020 to 2,150 ind/L, which is classified as moderate. The low dominance index (